Self-assembled Nucleic Acid Nanostructures for Biomedical Applications - Chang, Xu; Yang, Qi; Lee, Jungyeon; Zhang, Fei (Current Topics in Medicinal Chemistry, 2022)
Structural DNA nanotechnology has been developed into a powerful method for creating self-assembled nanomaterials. Their compatibility with biosystems, nanoscale addressability, and programmable dynamic features make them appealing candidates for biomedical research. This review paper focuses on DNA self-assembly strategies and designer nanostructures with custom functions for biomedical applications. Specifically, we review the development of DNA self-assembly methods, from simple DNA motifs consisting of a few DNA strands to complex DNA architectures assembled by DNA origami. Three advantages are discussed using structural DNA nanotechnology for biomedical applications: (1) precise spatial control, (2) molding and guiding other biomolecules, and (3) using reconfigurable DNA nanodevices to overcome biomedical challenges. Finally, we discuss the challenges and opportunities of employing DNA nanotechnology for biomedical applications, emphasizing diverse assembly strategies to create a custom DNA nanostructure with desired functions.
Keywords: Nucleic acid nanotechnology